Microbial screening and morphological analysis of the peat soil Gebeng, Malaysia - Al Jaber, Maryam; Nurmunira, Muhammad; Hajar Fauzan, Ahmad (IOP Publishing, 2025)
Peatlands are amongst the most critical ecosystems, representing hydrological, biological, and biogeochemical characteristics determined by water storage functions and greenhouse gas exchange. Peat soils have distinct problems of acidity, compressibility, and nutrient imbalances, which limit their agricultural, constructional, and environmental uses. Most current studies have focused on a single component, such as organic content, microbial diversity, and mineral composition, leading to a rather limited understanding. This paper combines microbial community screening with mineral and morphological analysis to evaluate various features and dynamics of peat soils and their uses, and therefore it brings new insights into the physical, chemical, and biological properties that concern its long-term use. The methodology entails collecting soil samples from various locations in Gebeng, Malaysia, and then determining their moisture content and pH. After that, it included the Morphological characterisation using Scanning electron microscope (SEM), Energy dispersive X-ray (EDX), powder X-ray diffractometry (XRD), and Fourier transform infrared spectroscopy (FTIR). Characterisation was then done, followed by DNA extraction and sequencing using the QIAamp PowerFecal Pro DNA Kit. The obtained research results, including SEM, showed that, in general, peat soil particles are poorly fragmented, the shape of which is irregular and heterogeneous with complex angularity rounded and elongated shapes, while the EDX analysis described a significant qualitative contrast. Also, XRD analysis discovered a complex mineralogical composition composed mainly of quartz (SiO2). Moreover, the tested peat samples showed a wide variety of inorganic salts, minerals, and organic components by FTIR examination. On the other hand, DNA sequencing results revealed richness in bacterial diversity in composition and relative abundances. This study generally has shown that Gebeng peat soil, with high organic matter content and diverse microbial populations, together with a reasonably balanced mineral input, potentially holds promising opportunities for agriculture and other industries such as construction, CO₂ reduction, and environmental management, but problems like acidity of soils, high compressibility, or nutrient imbalances require specified strategies in their management to be effectively exploited.